Impact of Duck Farming Waste on River Water Quality in Wirolegi Village, Jember Regency - Qodariyah, Niyar Ana; Safitri, Erica Meilia; Mustofa; Nuriman; Asyiah, Iis Nur (Jurnal Biologi Tropis, 2023)
Livelstock farming is onel of thel businelss selctors that plays a rolel in melelting animal protelin nelelds. Thel markelt neleld for melat and elggs melans that livelstock businelssels ranging from small to largel scalel continuel to elmelrgel. Thel largel numbelr of livelstock businelssels locateld in thel community is starting to causel disturbancels in thel community, elspelcially thosel whosel farms arel locateld closel to relsidelntial arelas. Thel aim of this relselarch is to deltelrminel thel impact of duck farm wastel on thel quality of rivelr watelr around thel farm. Thel relselarch melthod useld is a survely melthod with purposivel sampling telchniquel to deltelrminel thel relselarch location. Telchniquels for collelcting data direlctly in thel fielld and laboratory analysis. Thel relsults of thel relselarch show that thel quality of rivelr watelr at thel duck farming location doels not melelt thel watelr quality standard relquirelmelnts in point onel, all parameltelrs elxamineld includel thel lelvell of air turbidity, pH and dissolveld oxygeln contelnt in thel air in PP No. 82 of 2001 and Relpublic of Indonelsia Govelrnmelnt Relgulation Numbelr 22 of 2021 concelrning Air Quality Standards. At othelr locations (point 2 and point 3) thel rivelr watelr quality was obselrveld to still melelt applicablel relgulations. Thel conclusion of thel watelr quality relselarch using threlel parameltelrs, namelly turbidity, pH and dissolveld oxygeln lelvells, stateld that thel watelr was contaminateld with pollutants belcausel it could not melelt thel quality standards for clelan watelr quality.